The Nature, Extent, and Consequences of Genetic Variation in the opa Repeats of Notch in Drosophila - Rice, Clinton (G3 (Bethesda), 2015)
Polyglutamine (pQ) tracts are abundant in proteins co-interacting on DNA. The lengths of these pQ tracts can modulate their interaction strengths. However, pQ tracts >40 residues are pathologically prone to amyloidogenic self-assembly. Here, we assess the extent and consequences of variation in the pQ-encoding opa repeats of Notch in Drosophila melanogaster. We use Sanger sequencing to genotype opa sequences ([Formula: see text]-CAX repeats), which have resisted assembly using short sequence reads. While most sampled lines carry the major allele opa31 encoding Q(13)HQ(17) or the opa32 allele encoding Q(13)HQ(18), many lines carry rare alleles encoding pQ tracts >32 residues: opa33a (Q(14)HQ(18)), opa33b (Q(15)HQ(17)), opa34 (Q(16)HQ(17)), opa35a1/opa35a2 (Q(13)HQ(21)), opa36 (Q(13)HQ(22)), and opa37 (Q(13)HQ(23)). Only one rare allele encodes a tract <31 residues: opa23 (Q(13)–Q(10)). This opa23 allele shortens the pQ tract while simultaneously eliminating the interrupting histidine. We introgressed these opa variant alleles into common backgrounds and measured the frequency of Notch-type phenotypes. Homozygotes for the short and long opa alleles have defects in embryonic survival and sensory bristle organ patterning, and sometimes show wing notching. Consistent with functional differences between Notch opa variants, we find that a scute inversion carrying the rare opa33b allele suppresses the bristle patterning defect caused by achaete/scute insufficiency, while an equivalent scute inversion carrying opa31 manifests the patterning defect. Our results demonstrate the existence of potent pQ variants of Notch and the need for long read genotyping of key repeat variables underlying gene regulatory networks.